Hubungan Soft Skills terhadap Perencanaan Karier Mahasiswa - Muhammad Nikman Naser; Yopi Azhari Jayadi; Devi Haryani Putri; Septya Pransisca; Iktibar Iktibar (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Agama Islam Nahdlatul Wathan Samawa Sumbawa Besar, 2025)
This study aims to analyze the relationship between soft skills and career planning among students. Soft skills are believed to play an important role in helping students design their careers. The method used in this study is Pearson's correlation test to measure the degree of relationship between the two variables. The analysis results show that there is a significant and positive relationship between soft skills and career planning among students, with a correlation coefficient value of 0.671 (p=0.001), which indicates a strong relationship. This finding supports the hypothesis that mastery of soft skills can enhance students' readiness in planning their future careers. This study suggests that universities should focus more attention on developing soft skills through various educational programs and activities that support students' career readiness.